Leisure Involvement, Job Satisfaction, and Service Performance among Frontline Restaurant Employees. Issue 4 (4th July 2019) - Suhartanto, Dwi; Dean, David; Sumarjan, Nurzuwana; Kartika, Olivia Sri; Setiawati, Lina
ABSTRACT: The importance of employee leisure involvement to employee service performance has been suggested but not tested in the literature. This study closes this research gap by inspecting the direct consequence of leisure involvement on service performance and leisure involvement's indirect effect on service performance via job satisfaction for frontline service employees. This study uses a sample of 313 restaurant employees collected from Bandung, Indonesia. The proposed model is tested using variance-based SEM-PLS. The results show the importance of leisure involvement as a determinant of frontline service performance. Moreover, this study reveals that the effect of leisure involvement on service performance is partially mediated by job satisfaction. The conceptual and practical significance of these results are reviewed.